A Critical Dialogue of Structure and Reader in Romans 11: 16-24 - Maartend, P. J. (Hervormde teologiese studies, 1997)
A critical dialogue of structure and reader interprets Paul's allegory of the 'wild olive branches' beyond functionalistic methods of interpretation. Structuralism analyses the antithetical contrasts of the 'wild' and 'cultivated' branches, faith and unfaithfulness, and the kindness and severity of God which abounds in 'double parallelisms'. Reader semiotics identifies the recipient of grace ingrafted by God as participant in salvation. Grace shows no partiality of persons. The symbolism of 'wild olive branches' leads via the 'root' to the righteous servant as interpretant. Neither the Jews nor the Gentiles, as 'wild olive branches', have a claim to any 'prerogative of salvation'. The only privilege which prevails is one of service and allegiance to the divine call. The variegated perspectives generated by this analysis contribute to the polymorphous character of the meaning of the text. The critical dialogue of literary semiotics challenges the reader of every generation to enter into the ensuing debate and interpret the text in a way which is relevant to his/her historical context.